Pengaruh Laporan Keuangan sebagai Alat Perencanaan Laba Pada Pt. Perkebunan Nusantara Xiv (Persero) Pabrik Gula Camming Kabupaten Bone - Reskillah, Reskillah; Rustan Rustan; Rahayu Japar (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to predict the profit of PT Pabrik Gula Camming, located in Bone District, by analyzing the company’s financial statements from 2022 to 2024. The analytical tool used in this study is financial ratio analysis, which is applied to assess the company’s financial condition and performance. The ratios used in analyzing the financial statements include liquidity ratios, solvency ratios, activity ratios, and profitability ratios, based on the company’s balance sheet and income statement. In addition, profit forecasting is conducted using the contribution margin unit approach to determine the company’s ability to generate profit from its operational activities. Based on the results of data analysis, it can be seen that the profit planning of PT Pabrik Gula Camming has not been fully effective, as shown by the average sales percentage of 11.78%. These findings indicate that the company needs to improve financial planning, cost control, sales management, and operational efficiency in order to support better profit achievement in the future.